2020
DOI: 10.21608/adjg.2020.29055.1254
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Carbimazole on Parotid Acini of Albino Rats

Abstract: Purpose: This study aimed to study the effect of carbimazole on parotid acini. Materials and Methods: 20 adult albino rats were selected and divided into two groups: control group (GI) consisted of 10 rats received distilled water by intragastric intubation for 6 weeks and carbimazole group (GII) in which 10 rats received carbimazole dissolved in distilled water with a dose (1.35mg/kg bodyweight/once/ day) by intra-gastric intubation for 6 weeks. Results: GI illustrated normal histological features of acini. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…It was reported that reactive oxygen species attack the proteins and lipids that form the secretory granules membrane leading to its damage. In addition, they cause zymogen granules stability loss through an interaction with the protein contents and the nucleic acids of them (Hassan et al, 2021). Similar observations were demonstrated by Nasr El-Din &Abdel Fattah (2020) in hypothyroid rats and they were attributed to an increase in the Bax/Bcl-2 ratio.…”
Section: C-morphometric Resultssupporting
confidence: 77%
“…It was reported that reactive oxygen species attack the proteins and lipids that form the secretory granules membrane leading to its damage. In addition, they cause zymogen granules stability loss through an interaction with the protein contents and the nucleic acids of them (Hassan et al, 2021). Similar observations were demonstrated by Nasr El-Din &Abdel Fattah (2020) in hypothyroid rats and they were attributed to an increase in the Bax/Bcl-2 ratio.…”
Section: C-morphometric Resultssupporting
confidence: 77%